Impact of vaccine hesitancy on COVID-19 vaccination among the elderly in Beijing: a cross-sectional survey - Na GUO; Jiapeng CHEN; Xiaofeng JIANG; Huiwen LI; Ping ZHU; Yue BAI (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo understand the impact of vaccine hesitancy on coronavirus disease 2019 (COVID-19) vaccination status among the elderly population in Beijing, and to provide policy recommendations for the implementation of the national strategy to promote COVID-19 vaccination among the elderly. MethodsA stratified random sampling method was used to recruit 800 residents aged ≥ 60 years for a face-to-face survey in October 2020. A self-designed questionnaire was used to collect relevant information, and the 5C scale was used to capture relevant predictors of vaccination behavior among participants. Unconditional multivariate logistic regression models were used to analyze the effect of vaccine hesitancy on COVID-19 vaccination. ResultsOf the 720 eligible participants included in the analysis, 541 (75.14%) had received the first dose of COVID-19 vaccine. Participants' total score on the 5C scale was 4.84 ± 1.06 after positive and negative conversion, with dimensional scores of 8.94 ± 1.39 for confidence, 1.92 ± 2.26 for complacency, 1.46 ± 1.94 for constraints, 7.44 ± 2.63 for calculation, and 8.10 ± 1.68 for collective responsibility. The numbers (percentages) of participants classified as having high, moderate, and low vaccine hesitancy were 240 (33.33%), 232 (32.22%), and 248 (34.44%), respectively. After adjustment for sex, age, education, marital status, monthly household income per capita, smoking, alcohol consumption, social activities in the previous month, and chronic disease, the results of multivariable logistic regression indicated that participants with a higher collective responsibility score were more likely to have a higher COVID-19 vaccination rate (odds ratio [OR] = 1.21, 95% confidence interval [CI]: 1.00 - 1.46). In contrast, higher levels of complacency (OR = 0.76, 95%CI: 0.64 - 0.92), constraints (OR = 0.83, 95%CI: 0.69 - 0.99), and calculation (OR = 0.72, 95%CI: 0.58 - 0.89) were associated with lower vaccination rates. Participants with moderate and low vaccine hesitancy were more likely to be vaccinated, with an OR (95%CI) of 2.19 (1.44 - 3.33) and 4.03 (2.51 - 6.45), respectively. ConclusionThe COVID-19 vaccination rate among the elderly in Beijing is relatively low, with higher vaccination rates observed among those with lower levels of vaccine hesitancy.